Advancements and Innovative Strategies in Induced Pluripotent Stem Cell-Derived Mesenchymal Stem Cell Therapy: A Comprehensive Review - Xiaoyu Shi; Kun Zhang; Fengshi Yu; Qi Qi; Xiaoyu Cai; Yu Zhang (Hindawi Limited, 2024)
The effectiveness and safety of mesenchymal stem cell (MSC) therapy have been substantiated across various diseases. Nevertheless, challenges such as the restricted in vitro expansion capacity of tissue-derived MSCs and the clinical instability due to the high heterogeneity of isolated cells require urgent resolution. The induced pluripotent stem cell-derived MSCs (iPSC-MSCs), which is differentiated from iPSCs via specific experimental pathways, holds considerable potential as a substitute for tissue derived MSCs. Multiple studies have demonstrated that iPSCs can be differentiated into iPSC-MSCs through diverse differentiation strategies. Research suggests that iPSC-MSCs, when compared to tissue derived MSCs, exhibit superior characteristics in terms of proliferation ability, immune modulation capacity, and biological efficiency. In this review, we meticulously described and summarized the experimental methods of iPSC differentiation into iPSC-MSCs, the application of iPSC-MSCs in various disease models, the latest advancements in clinically relevant iPSC-derived cell products, and the development strategies for the next generation of iPSC-derived therapy products (not only cell products but also their derivatives).